Предмет: Математика,
автор: полиииии
ПОМОГИТЕ ПОЖАЛУЙСТА!!!
х+5-2(4-х)-х-4=
4(х+4)-5(2-х)-(5+4)х-3=
3(х+4)-3(5-х)-х-3=
4(х+3)-(2-х)-(1+4)х-2=
3(х+5)-4(5-х)-(4+3)х-1=
3(х+2)-4(1-х)-х-4=
4(х+2)-4(2-х)-4+4)х-3=
5(х+3)-3(1-4)-х-3=
2(х+4)-4(2-х)-(4+2)х-1=
4(х+1)-(5-х)-х-3=
Ответы
Автор ответа:
0
а в 7 скобри верно стоят?
Приложения:

Автор ответа:
0
упс
Похожие вопросы
Предмет: Геометрия,
автор: ulianasergeeva14
Предмет: Геометрия,
автор: 12341234786
Предмет: Английский язык,
автор: anonim27273
Предмет: Алгебра,
автор: korneushka